Sealing ability of mineral trioxide aggregate Plus™ and Biodentine™ for repair of furcal perforation in primary molars: An in vitro study - Farhin A Katge; Pooja Ravindra Shivasharan; Devendra Patil (Wolters Kluwer Medknow Publications, 2016)
Background: One of the unfavorable outcomes of endodontic treatment in primary molars is furcal perforation. During treatment, bacterial infection at the site of perforation should be prevented for better prognosis. Aim: This study aims to compare sealing ability of mineral trioxide aggregate (MTA) Plus™ and Biodentine™ for the repair of furcal perforation in primary molars using spectrophotometry. Materials and Methods: Access opening was done for all ninety extracted teeth. Perforation was made in furcation area in all the teeth. The sample size consisted of ninety extracted teeth. They were divided into four groups, Group 1 (n = 30) in which perforations were repaired with MTA Plus™, Group 2 (n = 30) in which perforations were repaired with Biodentine™. The other two groups were considered as control groups, Group 3 (n = 15) in which perforations were left unsealed (positive control) and Group 4 (n = 15) without perforations (negative control). Dye extraction method was used to compare the sealing ability of MTA Plus™ and Biodentine™. Statistical analysis was done using ANOVA test to compare the mean between the different groups. Intergroup comparison was performed using post hoc Scheffe test. Results: The highest dye absorbance was seen in the positive control group with a mean value of 0.080 ± 0.033. The mean value of MTA Plus™ was 0.031 ± 0.026 and Biodentine™ was 0.024 ± 0.031. Conclusion: The mean value of dye absorption of MTA Plus™ was greater than Biodentine™ but it was statistically insignificant.